An efficiency frontier based model for cloud computing provider selection and ranking - De Moraes L.B.* (2018)
Copyright © 2018 by SCITEPRESS - Science and Technology Publications, Lda. All rights reserved.Cloud computing become a successful service model that allows hosting and distribution of computational resources all around the world, via Internet and on demand. This success leveraged and popularized its adoption into all major IT companies. Based on this success, a large number of new companies were competitively created as providers of cloud computing services. This fact can difficult the customer ability to choose among those several cloud providers the most appropriate one to attend their requirements and computing needs. Therefore, this work aims to propose a model capable of selecting and ranking cloud providers according the analysis on the most efficient ones using a popular Multicriteria Decision Analysis (MCDA) method called Data Envelopment Analysis (DEA), that calculates efficiency using Linear Programming (LP) techniques. To accomplish that, the efficiency modeling is based on the analysis of each Performance Indicator (PI) values desired by the customer and the available ones in the cloud provider database. An example of the method's usage is given to illustrate the model operation, selection results and final provider ranking for five hypothetical customer requests and for ten providers.